Frozen Shoulder in Type 2 Diabetes Mellitus - Matloub, Atheer Ahmed; Al-Lehibi, Khalid I. Hussein (AL-Kindy College Medical Journal, 2010)
Background: Frozen shoulder affects 2-5% of thegeneral population, and around 10-30% of diabeticpatients. It affect mainly the non-dominant shoulder,and has more incidence in patients with poorglycemic control.Objective: To detect the incidence of frozenshoulder in type 2 diabetic patients attending theSpecialized Center for Endocrinology and Diabetesin Baghdad.Patients and methods: One hundredpatients with frozen shoulder were included in thestudy from a total number of 580 type 2 diabeticsover a period of six months. 70 patients werefemales and 30 patient were males. All wereinvestigated for fasting blood glucose and HbA1c.Results: The non-dominant shoulder wasinvolved in 60 patients (60%), the dominantshoulder in 35 patients (35%) and bilateralinvolvement in 5 patients (5%). 60 patients(60%) had poor glycemic control (HbA1c > 8%).Conclusion Diabetes mellitus is one of thepredisposing factors for the development offrozen shoulder which affect 17.2% of type 2diabetic patients in our study, most of them wereoverweight- obese and had poor glycemiccontrol